2007
DOI: 10.1007/s00267-007-9055-5
|View full text |Cite
|
Sign up to set email alerts
|

Human Influences on Water Quality in Great Lakes Coastal Wetlands

Abstract: A better understanding of relationships between human activities and water chemistry is needed to identify and manage sources of anthropogenic stress in Great Lakes coastal wetlands. The objective of the study described in this article was to characterize relationships between water chemistry and multiple classes of human activity (agriculture, population and development, point source pollution, and atmospheric deposition). We also evaluated the influence of geomorphology and biogeographic factors on stressor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 29 publications
5
58
2
1
Order By: Relevance
“…The CSI has been demonstrated to be strongly related to characteristics of diatom, bird, fish, amphibian, and coastal wetland vegetation communities (Reavie et al 2006, Brazner et al 2007). The constituent PCs of the CSI were also significantly related to coastal water chemistry (total P, total N, dissolved inorganic N, total suspended solids, and Cl À ) measured in 98 Great Lakes coastal wetlands (Morrice et al 2007). We adopted the CSI as an independent measure of watershed-scale anthropogenic stress based on its proven utility in prior studies, and did not attempt to evaluate or modify it.…”
Section: Site Environmental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSI has been demonstrated to be strongly related to characteristics of diatom, bird, fish, amphibian, and coastal wetland vegetation communities (Reavie et al 2006, Brazner et al 2007). The constituent PCs of the CSI were also significantly related to coastal water chemistry (total P, total N, dissolved inorganic N, total suspended solids, and Cl À ) measured in 98 Great Lakes coastal wetlands (Morrice et al 2007). We adopted the CSI as an independent measure of watershed-scale anthropogenic stress based on its proven utility in prior studies, and did not attempt to evaluate or modify it.…”
Section: Site Environmental Characterizationmentioning
confidence: 99%
“…Anthropogenic stressors may be activities that have occurred within the boundaries of the wetlands themselves, directly affecting wetland vegetation and function, or they may result from offsite activities in the landscape adjacent to the wetland, indirectly affecting coastal wetlands through fluxes of water, nutrients, and contaminants (Johnston 1994). An index of cumulative anthropogenic stress was developed for watersheds on the U.S. side of the Great Lakes basin by Danz and coworkers (2007) and was verified to be related to coastal wetland water quality (Morrice et al 2007) and biotic characteristics (Reavie et al 2006, Brazner et al 2007). Other studies have also confirmed that wetland vegetation is affected by upslope agriculture and urbanization (Findlay and Houlahan 1997, Mensing et al 1998, Galatowitsch et al 2000, Lougheed et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…We defined two human land-use variables as agriculture (including both pasture and row cropping) and urban land uses. Although there are other human disturbances that affect lakes, we use agriculture and urban land uses as indicators of many of the major human effects that influence water chemistry (Morrice et al 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that wetlands properly constructed and maintained could be effective for protecting water quality [25,26]. With several water quality stressors such as agriculture [27], urban development, population growth, and atmospheric deposition [28], the value of wetlands for water quality improvement is not unrealistic. Moreover, wetlands are central components of aquatic ecosystems, an interdependence that provides strong scientific justification for policies that make a connection between clean water and the protection of wetland ecosystems [29].…”
Section: Resultsmentioning
confidence: 99%